Protective role of N-acetylcysteine and Sulodexide on endothelial cells exposed on patients’ serum after SARS-CoV-2 infection - Rajewska-Tabor, Justyna; Sosińska-Zawierucha, Patrycja; Pyda, Malgorzata; Lesiak, Maciej; Bręborowicz, Andrzej (Frontiers in Cellular and Infection Microbiology, 2023)
Severe acute respiratory syndrome coronavirus-2 causes hyperinflammation and activation of coagulation cascade and, as a result, aggravates endothelial cell dysfunction. N-acetylcysteine and Sulodexide have been found to mitigate endothelial damage. The influence on coronary artery endothelial cells of serum collected after 4 ± 1 months from coronavirus infection was studied. The concentrations of serum samples of interleukin 6, von Willebrand Factor, tissue Plasminogen Activator, and Plasminogen Activator Inhibitor-1 were studied. The cultures with serum of patients after coronavirus infection were incubated with N-acetylcysteine and Sulodexide to estimate their potential protective role. The blood inflammatory parameters were increased in the group of cultures incubated with serum from patients after coronavirus infection. Supplementation of the serum from patients after coronavirus infection with N-acetylcysteine or Sulodexide reduced the synthesis of interleukin 6 and von Willebrand Factor. No changes in the synthesis of tissue Plasminogen Activator were observed. N-acetylcysteine reduced the synthesis of Plasminogen Activator Inhibitor-1. N-acetylcysteine and Sulodexide increased the tPA/PAI-1 ratio. N-acetylcysteine may have a role in reducing the myocardial injury occurring in the post-COVID-19 syndrome. Sulodexide can also play a protective role in post-COVID-19 patients.